Peningkatan Edukasi Masyarakat tentang Protokol Kesehatan dan Vaksinasi dalam Menjalankan Kegiatan New Normal di Majelis Taklim Masjid Nurul Huda Kota Padang - Muthmainnah Muthmainnah; Rahmi Muthia (Warta Pengabdian Andalas, 2022)
Community compliance to implement health protocols began to slacken in New Normal Period. This decrease in compliance is in line with the sloping rate of Covid-19 transmission in West Sumatra. There was a new case of Covid-19 again on November 1, 2021, after reaching a peak case during the pandemic. Education on social media such as TV, Facebook, and Instagram, which has been intensively carried out so far, has not been able to increase the knowledge and motivation of the community to carry out health protocols and Covid-19 vaccination. Based on the early observations, one community did not wear a face mask when doing activities due to a lack of trust in Covid-19. The results of further interviews with members of a social community found doubts about the Halal status of the current vaccination. Therefore, providing an educational method closer to the community was essential by attending group activities outside, such as Majelis Taklim at the Nurul Huda Mosque, Padang, West Sumatra. The educational method was implemented offline and given a pre-test and post-test to know the value. This activity was carried out on November 4, 2021. The results of the evaluation showed that there was an increase in public knowledge about health protocols and vaccinations in Padang.